Sosialisasi Wirausaha Digital Dan Menumbuhkan Jiwa Kewirausahaan Untuk Meningkatkan Minat Dan Motivasi Seorang Siswa SMKS 1 Pembangunan Kota Bengkulu - Febliansyah, M. Rahman; Abi, Yudi Irawan; Fitriano, Yun; Dary, Nadya Putri Wulan (Universitas Dehasen Bengkulu, 2024)
Digital entrepreneurship has made a tremendous impact in the world. Digital businesses are built through internet networks such as Google, Facebook, or other social media. Digitalization also has an impact on the development of new entrepreneurs. Socialization of Digital Entrepreneurship to Students of SMKS 1 Pembangunan Bengkulu City. It is an important step in preparing them to face this increasingly digital world of work. This service activity was carried out at SMKS 1 Pembangunan Bengkulu City on Friday, June 07, 2024. The implementation of this service activity is the socialization of digital entrepreneurship and fostering an entrepreneurial spirit to increase the interest and motivation of a student, At the socialization of digital entrepreneurship, students of SMKS 1 Pembangunan Bengkulu City are very likely to increase awareness of entrepreneurship at a young age, and must understand the challenges and multiply relationships and network connections are necessary. And what is more important to start this digital entrepreneurship is what skills and characters an entrepreneur must have in dealing with good and correct consumers. Problem solving through this socialization of digital entrepreneurship to SMKS 1 Pembangunan students of Bengkulu City is to encourage the creation of a culture that supports entrepreneurship and also increases awareness of innovation values to inspire students to become young entrepreneurs. From the problems in the service, students must be instilled with the values of innovation.